The Consumerism and Hedonism as the Root of the Decline in Environmental Support (Tasawuf and Ecology Review) - Handayani, Shinfi; Wafa, Muhammad Sidqul; Nur, Muhammad Azka; Hidayatullah, Ahmad Fauzan (UAS PRESS, 2024)
Consumerism is the habit of buying things that are less necessary, while hedonism refers to the idea that the main goal of life is happiness. These two behaviors are often related and have a negative influence on the environment. A review of Sufism and ecology will help us in understanding the consequences of consumerism and hedonism on the environment. Sufism provides a religious view of life, justice, and simplicity. Ecology includes aspects of the environment and life related to health, well-being, and balance. By examining the impact of consumerism and hedonism on the decline in the carrying capacity of the environment, and by utilizing the perspectives of Sufism and ecology. This research explores these concepts in the context of environmental sustainability and human well-being. Thus, this research is expected to provide new insights in efforts to overcome environmental challenges faced by modern society.